Proteomic analysis of a meningococcal outer membrane vesicle vaccine prepared from the group B strain NZ98/254. - Vipond, C; Suker, J; Jones, C; Tang, C; Feavers, I; Wheeler, J (2006)
In the absence of a suitable carbohydrate-based vaccine, outer membrane vesicle (OMV) vaccines have been used to disrupt outbreaks of serogroup B meningococcal disease for more than 20 years. Proteomic technology provides physical methods with the potential to assess the composition and consistency of these complex vaccines. 2-DE, combined with MS, were used to generate a proteome map of an OMV vaccine, developed to disrupt a long-running outbreak of group B disease in New Zealand. Seventy four spots from the protein map were identified including the outer membrane protein (OMP) antigens: PorA, PorB, RmpM and OpcA. Protein identification indicates that, in addition to OMPs, OMV vaccines contain periplasmic, membrane-associated and cytoplasmic proteins. 2-D-DIGE technology highlighted differences between preclinical development batches of vaccines from two different manufacturers.